Covid-19 Pandemic and Foreign Bank Performance in Asia-Pacific - Darynaufal Mulyaman; Farhan Julianto (Yayasan Riset dan Pengembangan Intelektual, 2021)
The covid-19 pandemic affects all aspects of human life, including the economy. Investments, transactions, and other financial services got a surprising shock as the effects of the pandemic. However, as time goes by, the pandemic starts to re-normalize turning into a new normal. Even, some countries in the Asia Pacific commencing a new-normal life, like, China, South Korea, and Singapore. Despite the good news, it seems the grassroots is not fully recovered from the shock. Therefore we argue that the positive outlook may not give a lot of positive senses and confidence, hence skepticism in the economy persists, especially in economic growth, despite some aspects, such as international banks or financial institutions in Asia set an optimist target. Further, this paper would like to explain the Behavioral Political Economy perspective and the case of CIMB Group in Indonesia for capturing regional political economy explanation and analyzed the relation of grassroots condition and the target’s positivism post the pandemic, as Indonesia is the second-largest market in the Asia Pacific and CIMB is one of the prominent universal bank groups in ASEAN and beyond.